Mechanics of rainfall infiltration through soil slope - Gofar, Nurly; Kassim, Azman (Faculty of Civil Engineering, 2008)
A sloping layered soil model consisting of a fine sandy silt layer over a coarse ‘jointed’ silty gravel was constructed inside a specially designed apparatus to study the mechanisms associated with capillary barrier effect for a two-layered soil system. In this study, simulated rainfalls of different intensities and durations representative of tropical climatic conditions were applied uniformly across the top surface of a tilting infiltration box of 2000mm in length, 1000mm in height and 100mm in width. The experimental result shows that the two-layer system under the influence of a high precipitation rate is primarily governed by the water retention capacity of the fine soil. At the interface along down slope, infiltration water retained in the upper layer of sandy silt and only constantly infiltrates into the lower layer after pore-water pressure increases to -8kPa. However, the observation of breakthrough at lower pore-water pressure corroborates the existence of a partial breakthrough region identified along the interface.